Partnership for prosperity and security in the Caribbean ([CCS] [Georgetown]GY, 1997)
Includes the Barbados Declaration of Principles and the Plan of Action which focuses on trade, development, finance and the environment, as well as on justice and security.
Available on CD Rom\n